G525(P) Wet cough in children with Severe Therapy Resistant Asthma (STRA). (27th April 2016) - Ali, SH; Nagakumar, P; Kenia, P; Rao, S
Abstract : Introduction: Severe therapy resistant asthma (STRA) accounts for a small subgroup of asthmatic asthma with significant morbidity and health care utilisation. The underlying immune pathological mechanisms are poorly understood (Bossley, JACI: 2012). Mucus hypersecretion is one of the pathophysiological features described in adult asthma but its role in paediatric STRA is unknown (Kuperman, Nat Med: 2002). We hypothesised that asthmatic children with wet cough have more severe disease compared to those without. Methods: An observational retrospective review of children with STRA (at step 5 of the SIGN/BTS guideline on asthma management, 2013) in a tertiary paediatric respiratory centre. All patients underwent protocol based STRA assessment. Data from 20 age-matched 6 to16-year-old STRA patients with wet cough were compared with those without wet cough (n = 21). All STRA patients with wet cough had additional investigations including CT chest scan, sweat test and immunological tests to exclude other underlying pathology. Spirometry, total and specific aeroallergen IgE, inhaled steroid and oral maintenance steroid dose, antibiotic use, infective and asthma exacerbations in preceding 12 months were included. All the data was collected +/- 3 months of the CT scan in patients with wet cough. Results: STRA patients with wet cough had similar weight, height and inhaled steroid dose compared to those without (Table 1 ). Patients with wet cough had significantly higher serum eosinophil counts (0.75 vs 0.45, p = 0.01) (Fig1) and higher number of infective episodes requiring antibiotics (1 vs 0, p = 0.001). 15% children had bronchiectasis and 35% had bronchial wall dilatation on scans. Patients with wet cough had lower lung function, higher total IgE and higher dose of maintenance oral steroids, although these parameters did not reach statistical significance (Table 1 ). Conclusion: We report a subgroup of STRA children with wet cough who have more troublesome symptoms and added treatment burden. This may represent a novel phenotype of paediatric STRA which may have different underlying immune mechanisms. Further prospective studies will help understand these and explore phenotype specific novel therapies.